Occlusal and cephalometric characteristics of anterior open-bite among Colombian 5-10 years old school children - María Ximena González; Ana Cristina Mafla (Universidad de Concepción., 2016)
Objetive. The aim of this study was to determine oclussal and skeletal characteristics of anterior open bite (AOB) according to sex and socioeconomic status (SES) in school children in the municipality of Pasto, Colombia. Methodology. A cross-sectional study was carried out involving 384 children between 5 and 10 years of age. A clinical assessment was performed to evaluate AOB, and information regarding socio-demographic variables, such as sex and SES according to Colombian standards, was obtained. Standardized lateral cephalograms and cast models were taken from participating subjects. A statistical analysis was performed using frequencies, percentages, t-student, ANOVA, Mann-Whitney and Kruskal-Wallis tests. Results. Prevalence of AOB was 8.1%, showing a significant difference according to SES. The most common Angle's classification was Class II with 70.6% in the right molars, and 58.8% in the left molars, according to occlusal characteristics. Statistically significant differences were observed in the ratio of posterior and anterior facial height (PFH:AFH) (p=0.050) according to sex. The distance between the upper first molar and palatal plane (U6-PP) (p=0.028), the Overbite (p=0.032) and Gonial° (p=0.033) values showed statistically significant differences according to SES in vertical skeletal measures. The 64.7% of AOB were of dental origin. Conclusion. Results suggest variations in some vertical skeletal measures according to sex and SES in children with AOB. Since a high percentage of AOB is caused by dental factors, preventive programs are required to control this condition.